Extracorporeal photopheresis: a useful therapy for patients with steroid‐refractory acute graft‐versus‐host disease but not for the prevention of the chronic form. (13th August 2013) - Rubegni, P.; Feci, L.; Poggiali, S.; Marotta, G.; D'Ascenzo, G.; Murdaca, F.; Fimiani, M.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Extracorporeal photopheresis (ECP) has been used successfully to treat severe steroid‐refractory acute and chronic graft‐versus‐host disease (aGVHD, cGVHD) since the late 1990s. What does this study add? ECP is effective in patients with mild to moderate steroid‐refractory aGVHD (grade II–III). On the other hand, ECP did not prevent the development of cGVHD in our patients.